A DEVELOPMENT OF NURSING CARE IN PATIENTS WITH PERIPHERAL INTRAVENOUS INFUSION AT MEDICAL INTENSIVE CARE UNIT, FACULTY OF MEDICINE RAMATHIBODI HOSPITAL - พนสิทธิวนา, วรันต์ภรณ์; ตั้งสุจริตวิจิตร, วิรัช; โตรักษา, สมชาติ (Journal of The Royal Thai Army Nurses, 2019)
Caring for patients in intensive care units (ICU) and preventing complications of peripheral intravenous infusion is crucial. This experimental development research of two groups with pre-test and post-test designs was aimed at developing a working model for nursing patients with peripheral intravenous infusion at the Medical Intensive Care Unit, Faculty of Medicine, Ramathibodi hospital. The research was conducted from June 16 to September 15, 2017. The control area was in the Cardiac Care Unit, Ramathibodi hospital. The sample of work was care implementation for patients with peripheral intravenous infusion during pre- and post-experimental phases in total of 167 times. The sample of participants included 69 service receivers, 47 service providers/nurses, and 2 managers. The nursing care was measured in 5 aspects: quantity, quality, duration, satisfaction of individuals involved, and economics. Data was analyzed using descriptive statistics, T-values, Paired T tests, Wilcoxon Signed-Rank test, Mann-Whitney U test with the alpha level at .05, and content analysis. The research findings revealed that the developed model applied 11 involved academics principles harmoniously with the context of the experimental area by using existing resources. The clearly written structures of workers, finance, equipment, and service systems helped the workers to understand and perform work by themselves. They were able to apply this model further in real contexts at Ramathibodi hospital, which emphasized simple but highly efficient work operations. The workflow chart to care for patients with peripheral intravenous infusion was clearly written by focusing on patient centeredness and nursing principles. After the experiment, the workers’ workload did not increase, but the accuracy rate to follow the standard increased (p=.003); work duration did not increase, the workers’ satisfaction did not decrease, and cost per service unit decreased (p<.001). For recommendations, the research should be continuously conducted throughout the entire hospital and developed to be a good working model of the country with higher efficiency. Policies on health service provisions should be more intense by focusing more on integrative work and multidisciplinary participation for patients to receive quality nursing care.